Examining "The end of revolution": a foretaste of Wang Hui’s thought - Horesh, Niv; Sullivan, Jonathan (SAGE, 2014)
Wang Hui is a significant contemporary Chinese thinker and a key representative of Chinese New Left thought. This article provides a critical review of some of the themes that emerge from Wang’s The End of Revolution as a means of situating his position in China’s intellectual landscape, with a particular mind to exploring the historicity of Wang’s thought as it informs his views. The essay engages some of the key discursive threads in The End of Revolution and provides a critical overview of Wang’s positions on neoliberalism, the tension between Western articulations of modernity and China’s own self-image.